GASTRIC PERFORATION MANAGEMENT IN A 50-YEAR-OLD PATIENT: A CASE STUDY (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Gastric perforation is one of the most common emergency conditions worldwide, with a mortality rate up to 30% and a morbidity rate up to 50%. World Health Organization data states that deaths due to gastric perforation in Indonesia reach 0.99%. Study is a case report, primary data obtained through anamnesis, physical examination, laboratory tests and x-ray examination. Assessment based on diagnosis holistic from the beginning, process and end of the study quantitatively and qualitatively. Subject case study was a 50-year-old man who came to the emergency room with pain all over stomach, especially in the upper left abdominal area. Pain was felt eight hours before entering the hospital. Abdominal pain felt like being stabbed, got worse when moving, coughing, or walking. Patients also complained of abdominal fullness and bloating. The patient has a personal and socioeconomic history which is a risk factor for gastric perforation, namely consumption of long-term non-steroidal anti-inflammatory pain relievers and smoking. Examination of the localized status of the abdomen found distention, muscular defans, tenderness throughout the abdominal field with dominant pain in the upper left abdomen, hepatic dullness disappeared, positive shifting dullness, and decreased bowel sounds. X-ray examination of the abdomen showed a picture of free air on the lateral side of the liver, suspicious for a pneumoperitoneum, preperitoneum fat line and psoas looked gloomy, suspicious for peritonitis. The patient was given pharmacological therapy in the form of injection of ceftriaxone 1 gram every 12 hours, infusion of metronidazole 500 mg every 8 hours, injection of omeprazole 40 mg every 12 hours, injection of ondansetron 4mg and sucralfate syrup 15 cc every 8 hours, followed by a laparotomy and closure of the perforated part. Postoperatively the patient was observed in the ICU for two days then transferred to a normal room after his condition stabilized.
Keywords: emergency; abdominal pain; gastric perforation